Comparison of the Inhibitory Binding Modes Between the Planar Fascaplysin and Its Nonplanar Tetrahydro-β-carboline Analogs in CDK4 - Liang, Yan; Quan, Huili; Bu, Tong; Li, Xuedong; Liu, Xingang; Wang, Songsong; He, Dian; Jia, Qingzhong; Zhang, Yang (Frontiers in Chemistry, 2021)
Fascaplysin is a natural marine product originating from sponges, attracting widespread attention due to its potential inhibitory activities against CDK4. However, its clinical application has been largely limited because of serious adverse effects caused by planar skeleton. To reduce the serious adverse effects, 18 tetrahydro-β-carboline analogs (compounds 6a-i and 7a-i) were designed and synthesized via breaking the planarity of fascaplysin, and the biological activities of the synthesized compounds were evaluated by MTT assay and CDK4/CycD3 enzyme inhibition assay. The title compounds showed varying degrees of inhibitory activities, especially the cytotoxicity of compound 6c against HeLa cells (IC50 = 1.03 ± 0.19 μM) with quite weak cytotoxicity toward the normal cells WI-38 (IC50 = 311.51 ± 56.06 μM), and the kinase inhibition test indicated that compound 6c was a potential CDK4 inhibitor. In order to further compare the action mechanisms of planar and nonplanar molecules on CDK4, the studied complexes of CDK4 bound with fascaplysin and three representative compounds (compound 6a-c) with bioactivities gradient were constructed by molecular docking and further verified through molecular dynamic simulation, which identified the key residues contributing to the ligands’ binding. By comparing the binding modes of the constructed systems, it could be found that the residues contributing significantly to compound 6c′s binding were highly consistent with those contributing significantly to fascaplysin’s binding. Through the design, synthesis of the nonplanar fascaplysin derivatives, and binding mechanism analysis, some valuable hints for the discovery of antitumor drug candidates could be provided.